1992
DOI: 10.1016/0014-5793(92)81500-l
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a novel protein‐tyrosine phosphatase SH‐PTP3 with sequence similarity to the src‐homology region 2

Abstract: Prorein-tyrosine phosphorylation and dcphosphorylntion are directly associated with cellular growlh. signal transduction, and ncoplastic trnnsformation. Here we report the isolation of a complementary DNA @DNA) clone encoding a novel protein-tyrosinc phosphatasc (PTP) from a human T cell PEER cDNA library. The predicted open reading frame encodes a -68.kDa protein composed of 593 amino acids which contains LWO src-homology region 2's (SH2 domains) at the N terminus; this PTP is dcsibflated as SH-PTP3. Northern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 26 publications
1
49
0
1
Order By: Relevance
“…SHP-2, previously called SH-PTP2, PTP1D, SH-PTP3, and Syp, was identified independently by several groups as a cytosolic SH2 domain containing protein tyrosine phosphatase [4][5][6][7][8]. It is ubiquitously expressed in various tissues and cell types.…”
Section: Signaling Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…SHP-2, previously called SH-PTP2, PTP1D, SH-PTP3, and Syp, was identified independently by several groups as a cytosolic SH2 domain containing protein tyrosine phosphatase [4][5][6][7][8]. It is ubiquitously expressed in various tissues and cell types.…”
Section: Signaling Mechanismsmentioning
confidence: 99%
“…However, studies regarding PTPs are lagging behind. SHP-2, a Src homology 2 (SH2) domain containing nontransmembrane PTP, has been demonstrated to be involved in a variety of cytokine and growth factor initiated signal transduction processes [4][5][6][7][8]. Increasing evidence has indicated that this phosphatase plays an important role in diverse signaling pathways to regulate cellular biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Another prominent one is the Akt pathway that seems to be important for the NF-kB activation (Sizemore et al, 1999;Ozes et al, 1999). In addition to Akt, SHP-2, a cytoplasmic tyrosine phosphatase containing SH2 domain (Freeman et al, 1992;Adachi et al, 1992), appears to modulate the NF-kB pathway (You et al, 2001). Although both the MEK1 -MAPK and the Akt-NF-kB pathways are critical for IL-1 and TNFa signaling, how they are activated remains to be explored.…”
mentioning
confidence: 99%
“…SHPTP1 appears to function primarily as a negative regulator of multiple hematopoietic cytokine and growth factor signaling pathways, as vividly illustrated by the motheaten mouse phenotype, which results from mutations in the SHPTP1 gene (62,71). The second mammalian SHPTP, SHPTP2 (17), also referred to as Syp (15), PTP-1D (76), PTP-2C (82), and SH-PTP3 (1), is ubiquitously expressed. Like SHPTP1, SHPTP2 contains two SH2 domains, a functional PTP domain, and a C-terminal hydrophilic domain containing tyrosyl phosphorylation sites (4).…”
mentioning
confidence: 99%